2010
DOI: 10.1210/en.2010-0336
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: Inflammation and Obesity Pathogenesis: The Hypothalamus Heats Up

Abstract: Obesity induced by high-fat (HF) feeding is associated with low-grade inflammation in peripheral tissues that predisposes to insulin resistance. Recent evidence suggests the occurrence of a similar process in the hypothalamus, which favors weight gain through impairment of leptin and insulin signaling. In addition to its implications for obesity pathogenesis, this hypothesis suggests that centrally targeted antiinflammatory therapies may prove effective in prevention and treatment of this disorder. This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
204
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(218 citation statements)
references
References 57 publications
10
204
1
3
Order By: Relevance
“…Suppression in the anterior insula activity on satiation suggests its role in feeding behaviour in addition to its taste sensory processing (22,25,(74)(75)(76) . The hypothalamus is widely recognised as the gatekeeper to control food intake, highly influenced by nutrients, with evidence that hypothalamic dysfunction may lead to obesity (77) . Prior studies have shown the hypothalamus is modulated by satiety (76,78) ; however this modulation is inconsistent across BOLD studies, and may be due to its small structure, variability in position and close proximity to the sinus cavity.…”
Section: Effect Of Hunger and Satiety On Functional Mri Responsementioning
confidence: 99%
“…Suppression in the anterior insula activity on satiation suggests its role in feeding behaviour in addition to its taste sensory processing (22,25,(74)(75)(76) . The hypothalamus is widely recognised as the gatekeeper to control food intake, highly influenced by nutrients, with evidence that hypothalamic dysfunction may lead to obesity (77) . Prior studies have shown the hypothalamus is modulated by satiety (76,78) ; however this modulation is inconsistent across BOLD studies, and may be due to its small structure, variability in position and close proximity to the sinus cavity.…”
Section: Effect Of Hunger and Satiety On Functional Mri Responsementioning
confidence: 99%
“…Some studies have shown that obesity is associated with inflammation in the hypothalamus (10)(11)(12)(13)(14), the central regulator of whole-body energy and glucose homeostasis (3)(4)(5)(6)(7)(8)(9). It appears that saturated fatty acids may directly activate toll-like receptor 4 (37), which subsequently leads to activation of the downstream JNK and IKKb/NF-kB cascade (13,17,38). In particular, modulation of the IKKb/NF-kB pathway at the level of IKKb and the upstream adaptor regulatory protein MyD88 suggested that this cascade, once activated, induces diet-induced resistance to the adiposity signals leptin and insulin (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is closely linked to several metabolic disorders including insulin resistance and type 2 diabetes (T2D) (1)(2)(3)(4)(5)(6). However, the mechanisms underlying obesity-associated insulin resistance are not fully understood.…”
mentioning
confidence: 99%
“…Recently, an emerging hypothesis suggests that the alteration of wholebody insulin sensitivity could have a starting point in the brain and precisely in the hypothalamus (7). Indeed, chronic high-fat feeding promotes hypothalamic resistance to leptin and insulin through an inflammatory-dependent mechanism leading to impaired energy homeostasis, obesity, and insulin resistance (4,7). Furthermore, compelling evidence indicates that changes in adipocyte-derived factors in obesity dramatically affect insulin sensitivity (4)(5)(6).…”
mentioning
confidence: 99%
See 1 more Smart Citation